THE The Contrıbutıon Of Csr To Advancıng Gender Empowerment Through The Women’s Lens - Nadia Nurul Azizah; Getar Hati (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Gender equality issue requires attention in Indonesia. To overcome the problem of gender inequality, women empowerment programs can be one of the strategic approach. This paper focuses on how the corporate social responsibility (CSR) program that focusing in women empowerment contribute the gender equality movement. Therefore, this paper highlights the contributions through women’s lens.. The research used data collection in-depth interviews technique with 10 informants from 3 areas in Jakarta. The research results various aspects such as changing perceptions regarding gender equality, understanding women's roles in the family and society, recognizing social support networks, and recognizing women's skills to support household income. Finally, this paper contributes to enrich the studies and practical work related to the implementation of CSR program in the framework of targeting the Sustainable Development Goals (SDGs).